Protein interactions during dry and wet heat pre-treatment of skim milk powder (dispersions) and their effect on the heat stability of recombined filled evaporated milk. (30th August 2023) - Wu, Jianfeng; Chen, Simin; Van Damme, Els J.M.; De Meulenaer, Bruno; Van der Meeren, Paul
Graphical abstract: Highlights: A suitable dry/wet heating of SMP (dispersions) imparted better RFEM heat stability. Prolonged incubation of SMP (dispersions) caused decreased RFEM heat stability. Protein interactions include WP-casein aggregation and casein dissociation. Decreased RFEM heat stability was related to formation of non-disulfide bonds. Decreased RFEM heat stability was related to protein carbonylation. Abstract: Skim milk powder (SMP) as well as aqueous dispersions were subjected to dry and wet heat pre-treatment, respectively, to improve the heat stability of recombined filled evaporated milk (RFEM) derived therefrom. However, microrheological analysis revealed that prolonged incubation caused detrimental effects on the heat stability of RFEM, which were thought to be due to protein interactions. SDS-PAGE results indicated that protein aggregation via non-disulfide covalent bonds occurred upon long-time dry or wet heat incubation. This was probably related to some Maillard reaction products, which is sustained by the increase in lactulose and protein carbonyl content. Considerable protein aggregation via disulfide bonds in the serum was found upon wet heat incubation at temperatures of at least 80 °C. Principal component analysis (PCA) revealed that the negative effects of overprocessing on the heat stability of RFEM were predominantly related to protein cross-linking via non-disulfide covalent bonds related to protein carbonylation.